Integrated task on students’ writing quality: Is it more effective? - Hieronimus Canggung Darong (English Language Teaching Educational Journal, 2021)
Integrated tasks are popularly known and accepted as an effective way of improving students’ writing quality. However, it is still not clear to what really accounts for its effectiveness. This study examined whether the students who were facilitated by integrated task achieved higher writing quality than those who were not. Twenty - two students participated within the group experiment utilizing a counterbalance technique in controlling the order effect. In the first session, twelve students were asked to write an essay based on an integrated (INT) task while the other 12 wrote based on an independent (IND) task. Then, the task division was switched in the second writing session. Students’ writing quality were scored by three raters and were analyzed descriptively and inferentially using Wilcoxon signed rank test (WSRT). The results confirmed that the quality of students’ writing using both integrated and independent tasks was not significantly different. There are still other aspects contributing to writing quality. Thus, task types do not guarantee the students’ writing quality.